16. ISOLASI Staphylococus aureus PENYEBAB BUMBLE FOOT PADA PERSENDIAN DAN TELAPAK KAKI AYAM JANTAN DI PASAR LAMBARO Isolation of Staphylococus aureus Causing Bumble Foot on Joints and Sole of Cocks in Lambaro Market - Erdi Rahmat (Universitas Syiah Kuala, 2016)
This research aimed to find out the Staphylococus areus in the joints and sole of cock suffered from bumble foot. This research used 20 feet of cocks selected from a traditional market of Lambaro subdistrict in Aceh Besar district. The samples were cleaned using 70% alcohol then the outer skin was removed. Suspected part infected by staphylococus aureus was cut into small in pieces. The piece was inoculated onto NB medium and incubated at 3? C for 48 hours. Bacteria that grew in NB medium was moved into MSA medium and incubated further at 37? C for 48 hours. The results of observation showed that Staphylococus aureus was found in 20 sample that were collected. ____________________________________________________________________________________________________________________ Key words: bumble foot, lambaro, Staphylococus aureus